A case control study on personality traits and disorders among deliberate self-harm patients in Malaysian hospital - Awang, Hamidin; Thambu, Maniam (Faculty of Medicine and Health Sciences, Universiti Putra Malaysia, 2008)
Objective: This study was conducted to compare the personality traits in deliberate self-harm (DSH) patients with a control group matched for age, sex and race. Methods: A case-control study design was used in this study. A total of 50 consecutive admissions to Kuala Lumpur Hospital following episodes of deliberate self-harm were compared with equal number of controls from the admission for minor medical illness during the same period. They were assessed on socio-demographic profile, Axis I psychiatric diagnosis and personality traits. Results: The mean age for the cases and controls was 26 years old. Seventy-eight percent of them were females, mostly unmarried and majority had completed their secondary education. The respondents were Indians (52%), Malays (40%) and Chinese (8%). A high prevalence of major depression (22%) was found among the cases compared to none among the controls. Personality disorders were present in 68% of cases as compared to 38% among the controls, while sensitivity (p<0.0005), impulsivity (p<0.0005), and worthlessness (p<0.0005) were the commonly reported personality traits. Paranoid personality disorder (p<0.05) and borderline personality disorder (p<0.05) were significantly present in deliberate self-harm subjects compared to the control group. Conclusion: Psychiatric disorder, personality traits of sensitivity, impulsivity and worthlessness, and personality disorders of paranoid and borderline were common in DSH patients.